Left ventricular volumes by echocardiography in chronic aortic and mitral regurgitations. (3rd May 2016) - Bech-Hanssen, Odd; Polte, Christian Lars; Lagerstrand, Kerstin M.; Johnsson, Åse A.; Fadel, Bahaa M.; Gao, Sinsia A.
ABSTRACT: Objectives Cut-off values for left ventricular (LV) dimensions indicating severe valve regurgitation have not been defined. The aim of this study was to establish echocardiographic cut-off values for LV dimensions indicating severe chronic aortic (AR) or mitral (MR) regurgitation.Design The hemodynamic significance was confirmed by documented reduction of end-diastolic volume (EDV) and symptom relief after surgery. Eighty-three patients with moderate or severe regurgitation (AR, n = 41; MR, n = 42) without other cardiac conditions underwent prospectively two-dimensional (2DE), real-time three-dimensional (RT3DE) echocardiography and cardiovascular magnetic resonance (CMR) exams within 4 h.Results The relationship between EDVCMR and EDV2DE and EDVRT3DE were strong (R 0.95 and 0.91). EDV index cut-offs for 2DE/RT3DE >87/104 ml/m 2 identified AR patients with severe regurgitation with a positive likelihood ratio (PLR) of 5.0/5.0. The corresponding in patients with MR EDV index cut-offs were >69/87 ml/m 2 with a PLR of 14.9/5.5. LV linear dimensions could not identify patients with severe regurgitation.Conclusions LV volumes by echocardiography can support the diagnosis of severe chronic regurgitation. Importantly, other causes for LV enlargement have to be considered.